2003
DOI: 10.1515/humr.2003.009
|View full text |Cite
|
Sign up to set email alerts
|

How many lesbians does it take to screw in a light bulb?

Abstract: This paper explores how humor reveals shared aspects of a culture of lesbian communities in the U.S. For lesbians, jokes and other forms of humor are an active, narrative means of self-construction and community imagining that help lesbians negotiate their positions both inside and outside mainstream culture. Whether consciously or unconsciously, much of lesbian humor challenges the dominant culture by rejecting its definitions of and presuppositions about lesbians, and by making lesbian experience central to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…While research has identified many cases in which sexual jokes are a means of female empowerment against the patriarchic society and the fixed, maleconstructed gender roles and hierarchies it imposes on women (Crawford 1995;Franzini 1996;Bing & Heller 2003;Reichenbach 2015), the jokes analyzed here mostly evidence their psychological function as an outlet that allows free expression of repressed, forbidden sexual impulses. Additionally, the analysis of the sexual jokes suggests that these particular examples work more as means of subordination and disempowerment of women, rather than tools of resistance to and challenge of male structured gender hierarchies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While research has identified many cases in which sexual jokes are a means of female empowerment against the patriarchic society and the fixed, maleconstructed gender roles and hierarchies it imposes on women (Crawford 1995;Franzini 1996;Bing & Heller 2003;Reichenbach 2015), the jokes analyzed here mostly evidence their psychological function as an outlet that allows free expression of repressed, forbidden sexual impulses. Additionally, the analysis of the sexual jokes suggests that these particular examples work more as means of subordination and disempowerment of women, rather than tools of resistance to and challenge of male structured gender hierarchies.…”
Section: Discussionmentioning
confidence: 99%
“…The relief function of jokes notwithstanding, more recent studies of feminist humor have elaborated on the manners in which such humor challenges traditional views of gender by targeting men, resists dominant constructions of femininity, as well as opposes gender inequalities and hegemonies in a patriarchal society with an aspiration to reform it (Crawford 1995(Crawford , 2003Franzini 1996). In a study on lesbian humor, Bing and Heller (2003) show how sexual humor can challenge dominant culture and its definitions and presuppositions about lesbianism. The authors demonstrate how lesbian jokes help lesbians construct and negotiate (homo)sexual identities as an empowering mechanism which through transformation, resistance, and subversion challenges dominant views and presuppositions.…”
Section: Sexual Jokesmentioning
confidence: 99%
“…Shaw's design theory is indicated by metadiscourse as she (Shaw, , p. 443; see also “Men illogical,” ) humorously states, “We used to believe that women were the sentimental sex, but they can not hold a tallow candle compared with the arc light of the men. Men are so sentimental in their attitude about women that they cannot reason about them.” Here, getting the joke depends on voters recognizing romantic relationship scripts (Bing & Heller, ) involving partners becoming less solicitous of each other over time, but that factor alone does not account for whether voters will openly appreciate the humor. Both proponents and opponents of woman suffrage charge the opposition with sentimentality and emotional excess.…”
Section: Discussionmentioning
confidence: 99%
“…Men are so sentimental in their attitude about women that they cannot reason about them." Here, getting the joke depends on voters recognizing romantic relationship scripts (Bing & Heller, 2003) involving partners becoming less solicitous of each other over time, but that factor alone does not account for whether voters will openly appreciate the humor. Both proponents and opponents of woman suffrage charge the opposition with sentimentality and emotional excess.…”
Section: Designing Political Humor To Take Seriouslymentioning
confidence: 99%
“…An even more complex example of the use of humor to create and maintain social structure is provided by Bing and Heller's (2003) analysis of lesbian humor, beginning with a variation on the familiar "lightbulb" joke, "How many lesbians does it take to screw in a lightbulb?" Bing and Heller relate and analyze several different punchlines, many of which play in one way or another on the sexual innuendo that nonlesbians would typically expect.…”
Section: The Role Of Humor and Irony In Meaning Creationmentioning
confidence: 99%